Synchronization of Poverty Reduction Program by TKPKD in Murung Raya District - Muliana; Muhammad Riduan Syafari; Muslih Amberi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
In line with this, the phenomenon that occurred in Central Kalimantan Province with macro achievement indicators below the national rate, namely the poverty rate of 5.17%, the Gini index of 0.342 and the Open Unemployment Rate of 4% below the national rate of 5.13%. Open unemployment in Central Kalimantan is still dominated by residents aged 15-19 years (high school age) at 31.52%. Meanwhile, Central Kalimantan's economic growth of 6.74% is still above the national economic growth of 5.27% where the welfare of the poor tends to be stagnant when compared to the upper middle class. Murung Raya Regency is one of the Regencies in Central Kalimantan Province, the Regency Capital is located in Puruk Cahu, This Regency is a division of North Barito Regency in 2002 with an area of 23,799 km2 and a population of 111,500 people. In this case it can also be described the data on the Poverty Line, Number, and Percentage of Poor Population in Murung Raya Regency, 2017-2021.